(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
A carapace of a new horseshoe crab (Arthropoda: Chelicerata: Xiphosura) is described from the Upper Carboniferous (Kasimovian) Meledis Formation of the Carnic Alps, Friuli, Italy. It is named as Stilpnocephalus pontebbanus n. gen. & n. sp., and belongs to the family Belinuridae Zittel in Zittel & Eastman, 1913. The large (>8 cm width) carapace is strongly effaced and appears to lack eyes. The new specimen is the first fossil horseshoe crab to be described from Italy and the largest known belinurid.